(untitled) (Chemical Engineering Research Bulletin, 2010)
In this paper, determination of material balance for reciprocal salt pair systems is considered and special case of KNO3 production is solved. A scheme is presented for calculation of material balance which is based on the conservation of ions and water. Material balance requires equilibrium composition and phase diagram of solid-liquid equilibria that is calculated by extended UNIQUAC thermodynamic model. Keywords: Fractional crystallization; KNO3 production; Material balance; Reciprocal Salt Pair systems DOI = 10.3329/cerb.v14i2.5542 Chemical Engineering Research Bulletin 14 (2010) 103-109